Gloss to the judgment of the Supreme Court of 24 February 2022, II CSKP 18/22 - Bączyk, Mirosław (Studia Iuridica Toruniensia, 2024)
The commentary presents a legal analysis of the possibilities and methods of changing the terms of a valid bank and insurance guarantee. This is a “guarantee of good performance of the contract concluded in professional transactions”, usually preceded by a so-called basic relationship as well as a guarantee mandate agreement. The above-mentioned changes usually comprise a validity period of guarantee, a guarantee sum and other elements of the agreement (e.g., the subject of protection). Nowadays, the changes of warranty conditions may be made in the same way as the moment a warranty contract is concluded. The possibility of such a change, usually provided for in standard contract terms, makes the bank guarantee an effective security instrument, which plays an important role due to its additional adaptive function. The author agrees with the judgement the Supreme Court that the beneficiary of the guarantee (an investor) does not accept a reduction of the guarantee sum.